Valor nutricional de la semilla de lupinus mutabilis proveniente de Otuzco, sometido a extrusión” - Padilla Velasquez, Orlando Edward (2017)
The seed of Lupinus mutabilis from Otuzco, submitted to Extrusion, was analyzed in order to know its nutritional value. It was determined Humidity and dry residue (gravimetric method of the stove), ashes (direct incineration), total proteins (Kjeldahl), carbohydrates (Fehling chemical method), fats (Soxhlet), calcium (complexometry) and iron (Munsey colorimetric with Phenanthroline). It was found that the seed of Lupinus mutabilis with shell and without shell from Otuzco subjected to Extrusion contain: 0.5% and 4.25% of humidity, respectively, 99.3% and 95.75% of dry residue, 1.37% and 1.34% of ash, 4.02% And 2.27% carbohydrates; 16.2% and 6.7% fat; 34.668% and 39.270% of total proteins; 10.75% and 10.65% calcium; And 1.21% and 0.53% of Iron, respectively. It is concluded that the seed of Lupinus mutabilis with shell and without shell coming from Otuzco, subjected to Extrusion, are important source of proteins and calcium